In vivo Bioluminescence Imaging Used to Monitor Disease Activity and Therapeutic Response in a Mouse Model of Tauopathy - Dunn-Meynell, Ambrose A.; Dowling, Peter; Marchese, Michelle; Rodriguez, Esther; Blumberg, Benjamin; Choi, Yun-Beom; Gaindh, Deeya; Lu, Wei (Frontiers in Aging Neuroscience, 2019)
Many studies of tauopathy use transgenic mice that overexpress the P301S mutant form of tau. Neuronal damage in these mice is associated with astrogliosis and induction of glial fibrillary acidic protein (GFAP) expression. GFAP-luc transgenic mice express firefly luciferase under the GFAP promoter, allowing bioluminescence to be measured non-invasively as a surrogate biomarker for astrogliosis. We bred double transgenic mice possessing both P301S and GFAP-luc cassettes and compared them to control mice bearing only the GFAP-luc transgene. We used serial bioluminescent images to define the onset and the time course of astrogliosis in these mice and this was correlated with the development of clinical deficit. Mice containing both GFAP-luc and P301S transgenes showed increased luminescence indicative of astroglial activation in the brain and spinal cord. Starting at 5 months old, the onset of clinical deterioration in these mice corresponded closely to the initial rise in the luminescent signal. Post mortem analysis showed the elevated luminescence was correlated with hyperphosphorylated tau deposition in the hippocampus of double transgenic mice. We used this method to determine the therapeutic effect of JM4 peptide (a small peptide immunomodulatory agent derived from human erythropoietin) on double transgenic mice. JM4 treatment significantly decreased the intensity of luminescence, neurological deficit and hyperphosphorylated tau in mice with both the P301S and GFAP-luc transgenes. These findings indicate that bioluminescence imaging is a powerful tool for quantifying GFAP expression in living P301S mice and can be used as a noninvasive biomarker of tau-induced neurodegeneration in preclinical therapeutic trials.